Doing Engineering: The Career Attainment and Mobility of Caucasian, Black, and Asian-American Engineers - Tang, Joyce (Rowman & Littlefield Publishers, 2000)
The first to systematically compare Caucasians, African Americans, and Asian Americans in engineering, this study of the career attainment and mobility of engineers in the United States tells how these three groups fare in the American engineering labor market and what they can look forward to in the future. The numbers of black and Asian engineers recently have grown at a much faster rate than the number of Caucasian engineers. With a projected steady increase in engineering jobs and demographic shifts, this trend should continue. Yet, recent writings on the engineering profession have said little about career mobility beyond graduation. This book identifies and explores key issues determining whether minorities in the US will attain occupational equality with their Caucasian counterparts. Highlighting implications for theory, policy making, and the future of the profession, Doing Engineering offers important insights into labor, race and ethnicity that will be of interest to anyone studying stratification in a wide range of professional occupations.